Influence of Cooking Technique on Bioaccessibility of Bioactive Compounds in Vegetable Lentil Soup - Sofía Vargha; Marta Igual; Marcelo Miraballes; Adriana Gámbaro; Purificación García-Segovia; Javier Martínez-Monzó (Foods, 2024)
Vegetables and legume soups contain various essential and bioactive constituents such as vitamin C, carotenoids, and phenolics. Antioxidant activity characteristics related to those compounds are well known to contribute profusely to human health. The cooking technique affects the bioavailability of nutrients and bioactive compounds, making it crucial to explore optimal alternatives to maximize them. The objective of this study was to explore the influence of different cooking techniques (boiling, pressure cooking, sous-vide, and cook-vide) on the physicochemical properties and bioactive characteristics of a ready-to-eat vegetable lentil soup. For this, the bioaccessibility of those compounds was assessed through an in vitro simulated gastrointestinal methodology. The firmness of vegetables was established to define treatments’ cooking times, allowing subsequent comparison of the nutritional and functional properties of the soups. The color of vegetables was also evaluated as a quality parameter, which contributed to providing a global vision of the process impact. The results revealed that in vitro digestion (IVD) caused a decrease in all bioactive compound determinations for all cooking treatments of up to 72% for total phenols, 92% for lycopene, 98% for carotenoids, and 100% for vitamin C. Additionally, the antioxidant activity of the soups after thermal treatment improved up to 46% measured by the DPPH method. This study emphasizes the importance of considering the digestion process in the selection of the most adequate cooking technique. After IVD, traditional cooking (boiling) reached the maximum total carotenoid and lycopene contents; cook-vide and pressure-cooking techniques provided the highest total phenol content, showing these three techniques to have the maximum antioxidant capacity.